Practices and perceptions of L1 and translation use: thematic analysis of a focus group interview with Kazakhstani secondary school EFL teachers (Journal of Educational Sciences, 2024)
From the latter half of the 20th century to the present day, monolingual or English-only teaching has been conventionally considered the optimal approach in English Language Teaching (ELT) literature and research. Nevertheless, there is a growing acknowledgement that mainstream ELT theory may offer a less precise portrayal of classroom dynamics than the actual observed reality. Consequently, this paper aims to explore teachers' practices and perceptions regarding the use of learners' first language (L1) and translation in EFL classrooms. A focus group interview (FGI) was conducted with in-service secondary school EFL teachers from Kazakhstan who were selected through non-probability sampling to achieve this goal. Thematic analysis was applied to scrutinize the interview data. The results revealed three primary themes: teaching English through L1, learners' English level and L1 use, and drawbacks of monolingual teaching. Each theme and sub-theme is substantiated by quotations from the interview and discussed in connection with ELT theory and relevant studies.Key words: L1 in ELT, translation in language teaching (TILT), translanguaging, multilingual teaching, teachers' practices, focus group, thematic analysis.